LANGUAGE STYLE ANALYSIS USED BY AGNEZ MO AND RICH BRYAN'S INTERVIEW ON ASIA POP AND BUILD SERIES - Bertaria Sohnata Hutauruk; Partohap Sibhombing; Febrika Dwi Lestari; David Togi Hutapea (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
This research is focused on language style analysis used by Agnes Mo and Rich Bryans Interview on Asia Pop and Build Series. This research aims to classify the type of language style and the most dominant types used by Agnes Mo and Rich Bryans Interview on Asia Pop and Build Series. The data source of this research was YouTube AGNEZ MO full length interview on Asia Pop 40 which was aired on September, 29th 2016 and Indonesian Rapper Rich Brian Chats About His Single, "100 Degrees," More which was aired on November, 21st 2019. This research used theories of language styles by Martin Joos. The data was collected from Script of Interviews video by Agnez Mo and Rich Bryan. The researcher applied a qualitative research design to answer the research question. The researcher used documentation as the research instrument. As the result of this research, the researcher found 30 data that contain language style. The researcher did not found frozen style (0) and found 4 types of language style in this research. The styles are formal style style 1 data (3%), consultative style 9 data (30%), casual style 19 data (64%) and intimate style 1 data (3%). The most dominant type of this research was casual style.